Crime and punishment in Colombia (2015)
During the 1990s, Colombia was considered one of the most violent countries in the world. Banditry, communist guerrilla groups, right?wing paramilitaries, drug cartels together with a sophisticated and versatile organized crime drew a violent landscape of murder. Although national homicide rate has fallen from 1995, Colombia remains a violent country. Scholars have tried to identify the causes of this entrenched and inveterate violence, without finding a definite answer. Practitioners have proposed few citizen security programs, often withering away and erratic, showing that there is no real policy with a strong leadership remaining. In contrast, the Colombian police force has played a pivotal role in dismantling numbers of delinquency networks and contributing to crime reduction.